2019
DOI: 10.1108/jec-12-2018-0099
|View full text |Cite
|
Sign up to set email alerts
|

The Buginese entrepreneurs; the influence of local values, motivation and entrepreneurial traits on business performance

Abstract: Purpose This study aims to investigate the role of Buginese cultural value system (BCVS), motivational values type (MVT) and entrepreneurial traits (ET) on business performance (BP). The study investigated the role of each variable in predicting BP among Buginese entrepreneurs. Design/methodology/approach The study was conducted in South Sulawesi, in small and medium scale enterprises with a focus on Buginese entrepreneurs. Random sampling technique was used along with some inclusion criteria. Based on those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
0
12
0
2
Order By: Relevance
“…Eastern Indonesia is predominantly influenced by the Bugis culture, which is distinct from Java or Jawa, the major ethnicity and culture in Indonesia. The Bugis people are implicitly influenced by their values and principles in performing business (Tamar et al, 2017(Tamar et al, , 2019. Considering the philosophical and cultural approach to authenticity (Algera and Lips-wiersma, 2012;Nyberg and Sveningsson, 2014;Shaw, 2010;Stewart et al, 2017), the employees in this study could have unique perspectives towards authenticity that could hinder the effect of leader's authenticity on work engagement.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Eastern Indonesia is predominantly influenced by the Bugis culture, which is distinct from Java or Jawa, the major ethnicity and culture in Indonesia. The Bugis people are implicitly influenced by their values and principles in performing business (Tamar et al, 2017(Tamar et al, , 2019. Considering the philosophical and cultural approach to authenticity (Algera and Lips-wiersma, 2012;Nyberg and Sveningsson, 2014;Shaw, 2010;Stewart et al, 2017), the employees in this study could have unique perspectives towards authenticity that could hinder the effect of leader's authenticity on work engagement.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, some studies also have documented that authentic leadership and PsyCap together predict positive and negative employee outcomes (Clapp-Smith et al, 2009;Laschinger and Fida, 2014;Rego et al, 2016;Woolley et al, 2011;Woolley et al, 2011). Considering the unique national values of Eastern Indonesia (Tamar et al, 2019) and how the national values support leadership (Oh et al, 2017), this study argues that authentic leadership and PsyCap will accrue work engagement by providing resources for employees; this country adapts local values in organisational practices.…”
Section: Psychological Capital (Psycap)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that when the values of employees or communities are aligned with the corporate culture, the process of establishing non-monetary incentive strategies as an effect of innovation-related actions is facilitated. It has been shown that in small businesses, non-financial factors can provide indicators for business success, such as personal values, satisfaction and achievements (Tamar et al , 2019). Taking into account that values and satisfaction are part of business success, they can be considered when proposing incentives for employees.…”
Section: Resultsmentioning
confidence: 99%
“…Culture has an effect in entrepreneurship motivations [40]; it is relevant for location-based businesses [41] and also for business performance [42]. Culture has been seen as increasingly important because it affects the organization of the enterprise, including the working climate, the capacity for innovation, and decision-making processes [16].…”
Section: Culture and Technological Knowledge In Ssbs Of La Manámentioning
confidence: 99%